Efficacy and safety of the Chinese herbal medicine Xiao-qing-long-tang for allergic rhinitis: A systematic review and meta-analysis of randomized controlled trials. (28th October 2022) - Yan, Yajie; Zhang, Jiajun; Liu, Haolan; Lin, Ze; Luo, Qiulan; Li, Yunying; Ruan, Yan; Zhou, Shiqing
Abstract: Ethnopharmacological relevance: The classic Chinese herbal medicine formula Xiao-qing-long-tang (XQLT) is commonly recommended to manage allergic rhinitis (AR), but the treatment efficacy and safety of XQLT are uncertain. Aim of the study: This study aimed to evaluate the effectiveness and safety of XQLT in treating AR. Materials and methods: Nine databases were searched from their inception to April 2021. Randomized controlled trials (RCTs) evaluating XQLT for AR were included. The methodological quality of the studies was assessed using the Cochrane risk-of-bias tool. A meta-analysis and a subgroup meta-analysis were conducted to evaluate the effectiveness of XQLT. Results: Twenty-four RCTs were included in this meta-analysis. XQLT was compared to both placebo and Western medicine (WM), and XQLT combined with WM was compared with WM alone. Meta-analyses were conducted for total nasal symptom scores (TNSS), four individual nasal symptom scores, quality of life (QoL), effective rate, and recurrence rate. The TNSS decreased after XQLT treatment and combination treatment (mean difference (MD): −0.79; 95% confidence interval (CI) [−1.20, −0.38], standardized mean difference (SMD): −1.42; 95% CI [−1.59, −1.24], and SMD: −1.84; 95% CI [−2.08, −1.60]). The two individual nasal symptom scores decreased after XQLT treatment and combination treatment; these nasal symptoms comprised rhinorrhea (SMD: −0.30; 95% CI [−0.58, −0.02] and SMD: −0.48; 95% CI [−0.70, −0.26]), and nasal obstruction (SMD: −0.54; 95% CI [−0.78, −0.30] and SMD: −0.54; 95% CI [−0.76, −0.32). XQLT and XQLT combined with WM achieved a better effective rate than WM (risk ratio (RR): 1.18; 95% CI [1.11, 1.25] and RR: 1.16; 95% CI [1.10, 1.23]) and a lower recurrence rate than WM (RR: 0.24; 95% CI [0.13, 0.43] and RR: 0.47; 95% CI [0.31, 0.72]). XQLT was well tolerated in patients being treated for AR. Conclusion: Our results indicated that oral XQLT may alleviate the TNSS, rhinorrhea scores, and nasal obstruction scores of AR and is safe to use in clinical practice. However, more RCTs that follow rigorous methodologies and evaluate well-accepted outcome measures are required to evaluate the effectiveness of XQLT. Graphical abstract: Image 1 Highlights: To our best knowledge, our study is the first systematic review and meta-analysis of XQLT on AR using RCTs. Our results indicated that oral XQLT may alleviate the symptoms of AR. Our results showed that XQLT is well tolerated and safe in patients treated for AR. XQLT may have better long-term effects of treatment of AR.